- STUDI KOMPARASI PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL(PERSELISIHAN HAK) MENURUT SISTEM HUKUM INDONESIA DAN KOREA SELATAN: - - Nina Stevany Malipolla; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2023)
Work contracts that are not in accordance with labour laws, discriminatory status and industrial relations, substandard wage rates and wage systems, and the non-fulfillment of other normative rights are examples of labour rights violations. Furthermore, this research is normative research that is descriptive in nature, with secondary data whose data sources are primary, secondary, and tertiary legal materials, qualitatively analyzed data collection through literature studies, and deductively derived conclusions. The problem statement in this research is how the similarities and differences between the rights conflicts in Indonesia and South Korea And how its advantages and disadvantages. The Labour Inspection Service is responsible for enforcing labor regulations that guarantee the fulfilment of labour rights and taking stern action against companies/employers who violate these regulations. As a result, labor rights violations continue to occur despite the Labour Inspection Service's efforts. Indonesia has permanent legal force where disputes can be resolved through litigation or non-litigation, and has deficiencies in terms of the type of settlement, whereas South Korea has more detailed legal force, but its weakness is that few cases of labour disputes are brought to court without going through the Labour Relations Commission (LRC).